Evaluation of quality of working life and its association with job performance of the nurses - Rastegari, Mohammad (Medknow Publications Pvt Ltd, 2010)
BACKGROUND: Nurses often complain about overwork and underpay. It seems that the association between “quality of working life” (QWL) and the degree of nurses’ involvement in their carrier is the critical factor in achieving a higher level of quality of care. This study aimed to assess the quality of working life and its association with “job performance” of the nurses in educational hospitals affiliated to Isfahan University of Medical Sciences in 2007. METHODS: This was a descriptive-correlation study. Target population included all the nurses who were employed in hospitals affiliated to Isfahan University of Medical Sciences. Sample size was 120 of the mentioned nurses. Sampling method was stratified random and data collection tool was a questionnaire. Data analysis was done using mean, frequency distribution and spearman test. RESULTS: Finding of the study showed that the most common kind of quality of working life in the nurses (56.7%) was moderate one. The most frequent nurses’ task performance (79.2%) was also related to the moderate performance. There was a direct and significant relationship between job performance and quality of working life in all the aspects. CONCLUSIONS: According to the research findings, it is important to consider the workplace and quality of working life of the nurses for improving productivity and performance of the nurses. Organization and nursing managers should use programs that can improve quality of working life of the nurses.